Spies without Cloaks : The KGB's Successors - Knight, Amy W., 1946- (Book collections on Project MUSE., 1998)
This book offers a compelling and comprehensive account of what happened to the KGB when the Soviet Union collapsed and the world's most powerful and dangerous secret police organization was uncloaked. As Amy Knight shows, the KGB was renamed and reorganized several times after it was officially disbanded in December 1991--but it was not reformed. Knight's rich and lively narrative begins with the aborted August 1991 coup, led by KGB hard-liners, and takes us through the summer of 1995, when the Russian parliamentary elections were looming on the horizon. The failed coup attempt was a setback.